Application of human computer interaction in developing an it-supported design collaboration process - Delavari, Naeimeh; Abdullah, Muhamad Taufik; Ibrahim, Rahinah; Sheik Said, Normahdiah (Universiti Putra Malaysia Press, 2013)
Increasing globalisation and international collaboration have led to an increaseddemand for improvedcommunication within design collaboration processes. To address this issue, IT-supported design collaboration processes have been utilised, enablingprofessional design team members to work in a distributed design environment. However, IT-supported systems often lack human understanding, making such systems frustrating for professionals to use.The objective of this theoretical paper is to propose Human-Computer Interaction (HCI) integrated approaches that improve the interaction among professional design team members and collaborative technologies in a distributed design environment. This is particularly examined in the context of the building industry. For this purpose,this paper analysesthe related literature in design collaboration processes. This analysis is used toassess how earlier systems affect design team members’ capabilitiesto accept and use collaborative technologies.It is found that in addition to impacting the ergonomic and cognitive capabilities of professionals, a system should also motivate professionals intrinsically and extrinsically. The findings of this study are essential forpromoting the utility of IT-supported design collaboration projects.In addition, this study supports further research to increase the level of engagement in collaborative team work and mitigate knowledge loss in a complex project lifecycle.